O GLORIAR-SE EM 2 CORÍNTIOS 12, 7 - 21 Auto-Glorificação ou Defesa da Honra - Frederico, Danielle Lucy Bósio (2012)
This search has as objective to analyze the use of the literary genre of glory by Paul Apostle, showing how this tool was essential for him to put himself in a radical and innovative way front to the accusations suffered by the Christian community in Corinth. This community under the influence of the traveling preachers, self-titled apostles, wanted to dishonor the Apostle while his was out. This community was a primitive Christian community in the Mediterranean of the First Century where the most valuable asset was the Honor and it should be defended above all. So, the Apostle used the act of glory, as a literary genre from his time, as well as other resources of rhetoric to defend himself. Doing that, the Apostle reframes the act of glory, the characteristic of a true apostle, as well as deal with suffering as something inherent to the faithful follower of Christ. This way, the Apostle(besides defending himself) exposes a new proposal on the understanding and experiences in the social relations which should go through renunciation to the status; forming an equal community.